2010
DOI: 10.1111/j.1439-0531.2008.01278.x
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbic Acid, Catalase and Chlorpromazine Reduce Cryopreservation-induced Damages to Crossbred Bull Spermatozoa

Abstract: The present study evaluated the effectiveness of ascorbic acid, catalase, chlorpromazine and their combinations in reducing the cryodamages to crossbred bull (Bos taurus x Bos indicus) spermatozoa. A total of 32 ejaculates (eight each from four bulls) were diluted in Tris-citric acid-fructose-egg yolk-glycerol extender. Each ejaculate was split into six parts (five treatment and one control). Treatment groups included 10 mm ascorbic acid, 0.1 mm chlorpromazine, 200 IU/ml catalase, 10 mm ascorbic acid + 0.1 mm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
22
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 21 publications
8
22
6
Order By: Relevance
“…Following freeze-thawing, there was a marked reduction in acrosin activity in both GFE and PFE, which was in agreement with the results of Pinart et al (2015). In fact, sperm cryopreservation is also known to significantly reduce acrosin activity in other mammals, such as humans (Cross and Hanks 1991), bulls (Paudel et al 2010) and bucks (Sirat et al 1996). However, the decrease in acrosin activity following freeze-thawing has been interpreted in a different manner by authors conducting their work in different species.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Following freeze-thawing, there was a marked reduction in acrosin activity in both GFE and PFE, which was in agreement with the results of Pinart et al (2015). In fact, sperm cryopreservation is also known to significantly reduce acrosin activity in other mammals, such as humans (Cross and Hanks 1991), bulls (Paudel et al 2010) and bucks (Sirat et al 1996). However, the decrease in acrosin activity following freeze-thawing has been interpreted in a different manner by authors conducting their work in different species.…”
Section: Discussionsupporting
confidence: 78%
“…Although no previous study has addressed this issue in cryopreserved spermatozoa from other mammalian species, different studies have evaluated the effects of other antioxidants. For example, Paudel et al (2010) showed that adding ascorbic acid, catalase and chlorpromazine to cryopreservation media not only reduced sperm cryodamage in bulls, but also better maintained their acrosin activity. In humans, Rao et al (2015) recently found that testicular hyperthermia increases oxidative stress and decreases acrosin activity.…”
Section: Discussionmentioning
confidence: 99%
“…Vc is another primary component of the antioxidant system. Vc can improve sperm viability, decrease the percentage of abnormality, and increase the activity of sperm motility (Dawson et al, 1992;Branco et al, 2010;Paudel et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This improves motility, viability and functional integrity of spermatozoa (Thiangtum et al. 2009; Paudel et al. 2010).…”
Section: Introductionmentioning
confidence: 99%